2021
DOI: 10.3390/agriculture11121206
|View full text |Cite
|
Sign up to set email alerts
|

R&D Innovation Adoption, Climatic Sensitivity, and Absorptive Ability Contribution for Agriculture TFP Growth in Pakistan

Abstract: Innovation adoptions in agriculture sustain high total factor productivity (TFP) growth and overcome a potential production gap, which is beneficial for food security. Research and development (R&D) innovation adoption in agriculture sector is dependent on producers’ willingness to adopt, knowledge capital spillovers, and financial capacity. This research aims to investigate the impact of R&D innovation adoption and climate factors on agriculture TFP growth in Pakistan. The annual time series data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Similar results are reported by Salim and Islam [ 21 ] for Australia, Tijani et al [ 43 ] for Nigeria, Dkhar and De [ 15 ] for Meghalaya, and Adetutu and Ajayi [ 44 ] for sub-Saharan Africa. In the context of Pakistan, the study conducted by Usman et al [ 45 ] focused on analysing the effects of R&D innovation and climatic variations on the overall factor productivity. The authors concluded that the adoption of agricultural R&D innovation has a notable and favourable impact on the agricultural productivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results are reported by Salim and Islam [ 21 ] for Australia, Tijani et al [ 43 ] for Nigeria, Dkhar and De [ 15 ] for Meghalaya, and Adetutu and Ajayi [ 44 ] for sub-Saharan Africa. In the context of Pakistan, the study conducted by Usman et al [ 45 ] focused on analysing the effects of R&D innovation and climatic variations on the overall factor productivity. The authors concluded that the adoption of agricultural R&D innovation has a notable and favourable impact on the agricultural productivity.…”
Section: Resultsmentioning
confidence: 99%
“…Specific to Pakistan, Usman, Hameed, Saboor, Almas and Hanif [ 31 ] examined the impact of R&D innovation and climatic changes on Pakistan's total factor productivity. Based on a time series of annual data from 1972 to 2020, the authors concluded that agricultural R&D innovation adoption had a significant positive effect on the total factor productivity of Pakistani farmers.…”
Section: Literature Review Research Gap and Hypotheses Formulationmentioning
confidence: 99%
“…From a global perspective, since the 19th century, scientific breeding has begun to rise, crop breeding has gradually developed into a relatively independent industry, and the degree of commercialization of seeds has been continuously improved. In the 1960s, in India, Pakistan, Mexico, and other regions of the world, the "green revolution" based on seed improvement technology to increase crop yield successfully verified the outstanding contribution of breeding technology to crop yield improvement, and further strengthened the following consensus: the public sector should bear an important responsibility in aquaculture [59,60]. However, cereal crops have been the focus of R&D expenditures in breeding programs, while edible legumes have been lacking in R&D expenditures [61].…”
Section: Data Sourcesmentioning
confidence: 96%
“…It includes research addressing aspects such as supportive public policies and the crucial role of extension agents, all within the framework of "sustainable agriculture, capacity building and training, or the role of gender in relation to the adoption of innovations (Bhatta et al, 2017;Branca & Perelli, 2020;Chatalova et al, 2017;Concu et al, 2020;Harun et al, 2021;Knierim et al, 2019;Mankad et al, 2017;Moglia et al, 2020;Ozcelik, 2016;Wedajo et al, 2019). Dissemination of knowledge to users is equally important (Harun et al, 2021;Rejesus & Jones, 2020;Usman et al, 2021). Indeed, technology adoption and sustainable agriculture are two concepts that are commonly linked in the scientific literature about the diffusion and adoption of agricultural innovations and have often been studied in developing countries (Onyancha & Onyango, 2020;Yamoah et al, 2020).…”
Section: Developing Countries and Decision Makingmentioning
confidence: 99%